Influence Of Different Determination Of 1,2,4-Triazols On The Growth, Development And Yield Of Grain Sorghum - Bihdan, O. A.; Gotsulya, A. S.; Parchenko, V. V.; Izhboldin, O.; Бігдан, Олексій Антонович; Гоцуля, Андрій Сергійович; Парченко, Володимир Володимирович (My University, 2019)
The publishing activity of scientists practically around the world about the properties of derivatives of 1,2,4-triazole makes it possible to assert with certainty that this class of heterocyclic systems is very promising. 1,2,4-triazoles have proven themselves as biologically active compounds, plant growth regulators, anti-corrosion agents, plastic plasticizers, and other. In addition, they are practically non-toxic and highly reactive due to the presence of reactionary centers in them [1, 2].
Keywords: yield of sorghum; hybrids of Keiras and Fulgus; water soluble derivatives of 1,2,4-triazole; growth stimulating properties